EKSKLUSI ATAS NAMA KONSERVASI (Studi Kasus Masyarakat Sekitar/Dalam Kawasan Taman Nasional Ujungkulon Banten) - Eko Cahyono (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
This paper elaborate on the issue of conservation, agrarian conflict and exclusion communities around / in the conservation area of the National Park Ujungkulon (TNUK) Banten. The issue of paradigm for governance natural resources is the source and root of behavior, policy, and conservation programs are iqnorance of rights, access, control and life space people around / in the conservation area. Then it will be explained why it matters and how exclusion processes occurred, and the reason and what the paradigm, what conditions pushed, contestation actors and interests and how the public response, and how its impact on society in surroundings. This paper concludes with a reflection on the state of denial over its natural resources and agrarian resources themselves.